Persepsi Mahasiswa Terhadap Metoda Demonstrasi dan Media Visual dalam Peningkatan Kompetensi Penataan Sanggul Modern pada Mahasiswa Pendidikan Tata Kecantikan - Trisnani Widowati (Peneliti.net, 2020)
The purpose of this study is to describe students' perceptions of the demonstration method and visual media in improving the competence of modern bun bun on beauty education students. This research is a descriptive analysis with 5 beauty education participants. The type of data needed is direct data, this data is obtained based on a questionnaire obtained by data analysis, then processed and interpreted, taken from the percentage. This research is a quantitative descriptive study, using data collection techniques that are questionnaires or questionnaires as well as assistance as supporting research dataThe results of this study indicate, students' perceptions of the demonstration method and visual media in enhancing the competence of modern bun structuring in beauty education students have good quality (70%). Based on the results of student research, they prefer demonstration methods and visual media that are carried out in conjunction with the implementation of concepts and development.